Recent Emergence and Re-Emergence of Crimean Congo Hemorrhagic Fever and Q Fever Zoonotic Diseases: Major yet Ignored Infectious Diseases Worldwide - Abdolmajid Ghasemian; Shaden MH Mubarak; Mojtaba Memarian; Hamed Memarian; Sarvenaz Falsafi; Najafiolya Zahra; Shokouhi Mostafavi Seyyed Khalil (Fasa University of Medical Sciences, 2022)
The continuing emergence or re-emergence of vector-borne zoonotic Q fever (caused by Coxiella burnetii) and Crimean Congo hemorrhagic fever (CCHF, caused by Orthonairovirus) include indispensable extraordinary threat around the world. Low infectious dose and long-term environmental residence are major risks. Wildlife and domestic livestock act as hosts or reservoirs of the CCHF virus and ticks are carriers. The disease also poses a threat to public health services owing to its epidemic potential, high case fatality ratio (up to 40%) as well as difficulties in treatment, prevention, and control. Q fever is another zoonotic febrile disease mainly affecting workers involved in farming livestock. The causative agent of Q fever causes abortion in livestock. The pathogen is shed in large numbers in the waste of infected animals (amniotic fluids and placenta during parturition) and is transmitted by inhalation of contaminated aerosols. Vaccination is the most effective way of protecting against Q fever. The main way to prevent Q fever is to avoid contact with animals, especially while animals are giving birth, or consumption of unpasteurized milk and contaminated dairy products. Due to the increasing importation of livestock to meet the growing demand for dairy and meat products, new diseases are likely to be introduced. In our growing globalized world, where trade between countries increases, it is necessary to conduct more research on zoonotic diseases and to monitor any possible disease introduction to new areas. A continuing surveillance program and pathogen testing are important in tracking the emergence of new pathogens.